Bis-indole derivatives with antitumor activity turn out to be specific ligands of human telomeric G-quadruplex - Amato, Jussara; Iaccarino, Nunzia; Pagano, Bruno; Morigi, Rita; Locatelli, Alessandra; Leoni, Alberto; Rambaldi, Mirella; Zizza, Pasquale; Biroccio, Annamaria; Novellino, Ettore; Randazzo, Antonio (Frontiers in Chemistry, 2014)
Bis-indolinone derivatives having either 2,6-disubstituted pyridine core (1a and 1b) or 1,10-disubstituted phenanthroline core (2a and 2b), already known to have antitumor activity, have been tested as potential G-quadruplex binders. Compounds 2a and 2b are able to selectively stabilize G-quadruplex over duplex DNA, and also to discriminate among different G-quadruplex structures, having a particular affinity for the parallel form of the human telomeric G-quadruplex. Both compounds are also able to induce telomeric DNA damage that may explain the activity of these compounds.